A girl named Helen Keller - Lundell, Margo; Trivas, Irene (New York : Scholastic, 1995)
Recounts the life of Helen Keller, who had lost her sight and hearing by age 2, focusing on her early childhood and how her teacher Anne Sullivan succeeded in teaching her to understand the manual alphabet.
I
520
I
Keywords: Deafblind women -- United States -- Biography -- Juvenile literature; Blind; Deaf; People with disabilities; Women -- Biography